The Association Between Hypertension and Stroke in PKU Muhammadiyah Gamping Hospital - Intan Dyah Prawesti; Andrianto Selohandono; Ario Tejosukmono; Novi Wijayanti Sukirto; Rachma Greta Perdana Putri (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Stroke is a non-communicable disease whose annual incidence or prevalence continues to increase, with one of the causes being hypertension. Hypertension is a condition of increased blood pressure, if not controlled, can lead to complications. The incidence of stroke in Sleman Regency reaches 10,4% and the incidence of hypertension in Sleman Regency reaches 23,7%.Objective: This research aims to determine the relationship between patients who have hypertension with the occurrence of stroke.Methods: This research is a quantitative analytic study using a cross-sectional design. The population is all stroke patients at PKU Muhammadiyah Gamping Hospital, with a sample of 99 patients and the data collection technique used is purposive sampling. The research data was taken using medical records.Results: The result showed that the majority of patients had hemorrhagic stroke (62,6%) with grade 3 hypertension (37,3%). The odds ratio (OR) for hypertension grade 3 has a risk of 7,153 times having a stroke compared to grade 1 hypertension. The p-value for hypertension 1 and hypertension 3 is 0,001 (p<0,005) which indicates a significant relationship between higher grade hypertension and the incidence of hemorrhagic stroke. Conclusion: There is a relationship between higher grade hypertension and the incidence of hemorrhagic stroke